Development Of Teaching Materials Using A Scientific And Contextual Approach To Improve Mathematic Connection Ability - Pamila Malinda; Euis Eti Rohaeti; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
For students learning mathematics, mastery of concepts is important, one of which relates one concept to another. One of the abilities that students must have is the ability to connect mathematically, but it turns out that the facts in the field are still relatively low. In order to improve the learning process, a combination of scientific and contextual approaches can be used by developing teaching materials. This study aims to develop teaching materials using a combination of scientific and contextual approaches to improve the mathematical connection skills of junior high school students, the method used is Research and Development (R&D) ADDIE model. The results obtained from the limited and wider trial validity are valid and feasible to be used at the product testing stage, at the limited trial stage the practicality of lesson plans and worksheets by teachers is in the practical category and at the wider trial stage it is in the very practical category, the practicality of Student Worksheets by students at the limited trial stage and more broadly is in the practical category, The effectiveness was in the quite effective category in the limited trial stage, and it was in the effective category in the wider trial stage, then the implementation in the limited trial stage obtained a percentage of 81.2% and in the wider trial stage a percentage of 89.7% was obtained and for increasing mathematical connection ability, the N-Gain was 0.58 which was included in the medium category.